Penta Helix Model: Developing Economic Potential Through Halal Tourism And Local Cuisine Padangsidempuan City - Mery Octavianna Lubis, Rizky; Maya Mei Shanty, Ade (Jurnal Ekonomi, 2024)
Tourism acknowledges the growing interest in Halal tourism, both from an industry and research. Regional wisdom is needed to approach development holistically to achieve equitable progress in economic, ecological, and social justice aspects. To enhance tourism growth, several elements must collaborate with stakeholders, a concept known as the "pentahelix." This research is a qualitative study, collects data from informants by interview method who are part of the pentahelix stakeholders: Academics, Government, Business, Community, and Media. Based on the results, the collaboration among the roles of the Pentahelix Model in the development of tourism in Padangsidempuan city is operating optimally. Academics, as Conceptors; Business, as Enablers; The Community acts as Accelerators; The Government, as Regulators, has organized activities funded by special allocation funds to support the development of halal tourism and cuisine in Padangsidempuan. Media, as Expanders, has created a brand image through its programs broadcasted on social media platforms.